PERFORMANCE TESTING ON WEB INFORMATION SYSTEM USING APACHE JMETER AND BLAZEMETER - Indrianto, Indrianto (LPPM Universitas Jambi, 2023)
The Abiansemal Bali Global Vocational School Teacher Information System is a web-based application that makes teachers' work easier, which is the implementation of applied science in the field of technology. As the number of teachers increases, server performance needs to be evaluated to ensure it can handle requests from each teacher. This research tested the performance of an Information System Website using two tools, namely Apache JMeter and BlazeMeter. This test includes four modules: login page, updating teacher profile, uploading images, and creating questions. Testing uses 50 and 100 samples with a ramp-up period of 10 seconds and several loops of 1. Test results show that the system works well on these modules, with a stable average response time, increased throughput, and decreased deviation. This information reveals system performance and can help make improvements and optimizations to improve the speed and quality of the user experience. Performance testing with Apache JMeter and BlazeMeter is a useful method for testing the performance of web-based information systems.